The Effect of Lactobacillus gasseri Against Pseudomonas aeruginosa Infection in Mice. - AL- Marjani, M. F.; Abdul-Jabbar, R. A.A.; Hassan, A.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of local Lactobacillus gasseri filtrate against Pseudomonas aeruginosa infection in mice was studied . 0.25 ml of concentrated filtrate Lactobacillus gasseri was injected in intraperitoneally ( I.P.) 5 days before challenge with 0.2 ml viable P. aeruginosa ( 10 8 cell/ ml). Animals were sacrificed after 12 h. from challenge by cutting the femoral artery . To follow bacterial growth in the peritoneal cavity , its contents were washed out with 5 ml of PBS .The fluid was diluted, 0.1 ml from each dilution and was spread on culture media. The number of colonies in 5 ml of harvested fluid was expressed as Log 10 CFU ,and the percentage of Macrophage in the peritoneal cavity was counted. Growth of P. aeruginosa in the peritoneal cavity was markedly inhibited in Lb. gasseri pretreated mice, wherease such inhibition of bacterial growth was not observed in another group ( mice were not treated with Lb. gasseri ) The percentage of macrophage detectable in the peritoneal cavity was 18% in control and 27% in test . It was suggested that macrophages activated with Lb. gasseri were involved in the protective to P. aeruginosa.